2010
DOI: 10.1002/jso.21774
|View full text |Cite
|
Sign up to set email alerts
|

High sacrectomy for locally recurrent rectal cancer: Can long‐term survival be achieved?

Abstract: High sacrectomy that achieves clear margins in patients with recurrent rectal cancer is safe and feasible. A majority will die of metastatic disease, but long-term survival may be possible in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 38 publications
2
51
0
1
Order By: Relevance
“…After screening, 16 studies were found to be eligible for inclusion (1 prospective cohort study on radiosurgery (level II) [32]; 2 case series (level III) [28,33]; 4 retrospective case series (level IV) [2,10,34,35] and 9 case reports (level IV) [36][37][38][39][40][41][42][43][44]; Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 16 studies were found to be eligible for inclusion (1 prospective cohort study on radiosurgery (level II) [32]; 2 case series (level III) [28,33]; 4 retrospective case series (level IV) [2,10,34,35] and 9 case reports (level IV) [36][37][38][39][40][41][42][43][44]; Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Six studies report on their results of surgery ranging from posterior decompression with(out) cementation and instrumentation [2,28,35,43] to abdominal sacral resection [33] and en bloc sacrectomy [34,44].…”
Section: Treatmentmentioning
confidence: 99%
“…32 Long-term survival may be feasible in select patients with recurrent metastatic rectal cancer if margin-negative resection is achieved. 12,36 Furthermore, giant cell tumors, 19 primary sacral osteosarcomas, 34 and sacral chordomas 14 have been shown to be amenable to sacral resection, with reports of prolonged survival and functional recovery.…”
Section: Combined Vram and Free Fibular Flapsmentioning
confidence: 99%
“…Правда, авторы подобных публикаций не ссылаются на контролируемые рандомизированные исследования и не проводят какой-либо статистической оценки рисков осложнений. Дру-гие исследователи считают такие операции допустимы-ми, указывая в качестве аргумента собственный опыт их выполнения [11].…”
Section: However the Choice Of Tactics For This Patient Category Remunclassified